Burundi Digital Economy Assessment - World Bank Group (World Bank, Washington, DC, 2021)
Coronavirus 2019 (COVID-19) has highlighted the need for accelerating digital adoption in Burundi. Burundi’s current sectoral strategies acknowledge the importance of investing in digital technology. However, these lack an overarching approach with an actionable roadmap and clear resources behind it. Burundi’s mobile network coverage and mobile broadband uptake continues to be characterized by a stark urban-rural divide. Digital platforms are paramount in connecting people, businesses, and the government - enabling both transactions and the exchange of information, goods, and services in more efficient and convenient ways. At present Burundi’s digital entrepreneurship sector remains embryonic, hampered by barriers such as limited ecosystem support and weak access to financing. Whether through the provision of public services closer to its citizens with digital platforms, or through increased financial inclusion enabled by digital financial services and dynamic digital ecosystems, Burundi stands to gain from a continued investment in the foundations of its digital economy. Chapter one gives introduction. Chapter two reviews cross-cutting factors that affect the strategic, institutional, and regulatory environment for the digital agenda in Burundi. The report proceeds to explore the five foundational pillars of the digital economy, in more depth. Chapter three looks at the access, quality, and usage of digital infrastructure, as well as the dynamics of the connectivity market, including what it will take to get more Burundians online. Chapter four discusses the current state of digital skills attainment and coverage. Chapter five analyzes the current application and scope for expanding the use of digital platforms - both in the public and private sector. Chapter six examines the state and uptake of digital financial services (DFS) among individuals, businesses and by government. Finally, chapter seven assesses the state of digital entrepreneurship and the culture of innovation in Burundi.